Plasma protection composite coating with nanostructure and preparation method
By preparing a nanostructured yttrium oxide composite coating on the substrate and combining it with vacuum cold spraying and heat treatment processes, the problems of poor etching resistance and high cost of existing plasma protective coatings in high-power plasma etching environments are solved, and a plasma protection effect with high density, excellent insulation and long life is achieved.
Patent Information
- Application Number
- CN202511255060.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-04
- Publication Date
- 2025-10-03
- Estimated Expiration
- 2045-09-04
AI Technical Summary
Existing plasma protective coatings have problems such as poor etching resistance, insufficient density, weak bonding, poor thermal stability and high cost in high-power plasma etching environments, especially in advanced chip manufacturing processes of 5nm and below, resulting in reduced device yield and shortened equipment life.
A thin yttrium oxide composite coating is prepared on the substrate by vacuum cold spraying method, and combined with heat treatment process. The coating material consists of yttrium oxide and a second ceramic component. The powders are mixed by mechanical ball milling and coated to form a nanostructured composite coating.
It improves the density and thermal shock resistance of the coating, reduces particle contamination, enhances the bonding strength and etching resistance of the coating, reduces preparation costs, extends device life and improves the process window.
Smart Images

Figure CN120736898A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of surface protection in the process of manufacturing semiconductor devices, and in particular to a nanostructured plasma protection composite coating and a preparation method thereof. Background Art
[0002] As semiconductor devices evolve toward higher integration and smaller dimensions, plasma etching, a key pattern transfer process, is experiencing a shift toward higher energy density, higher frequency, and more reactive environments. This places stricter demands on surface selective etching, protective stability, and heat transfer resistance. In particular, in advanced chip manufacturing processes (5nm and below), fluorine-based plasmas have become a mainstream etching medium due to their high etch rate, strong anisotropy, and wide range of applications. However, the highly corrosive nature of fluorine-based plasmas can lead to rapid failure of the inner walls and components of etching equipment chambers, causing particle contamination and process drift, severely limiting semiconductor device yield and equipment lifespan. Therefore, the development of new, high-performance plasma etching protection technologies has become a key bottleneck.
[0003] In the early days, to address the severe corrosion caused by plasma, anodic aluminum oxide passivation films or sintered ceramic sheets were mainly used. However, these materials exposed significant defects under the strong corrosion of high-power fluorine / chlorine plasmas (such as CF4 / O2, Cl2). Since the 1990s, thermal spraying ceramic coating technology (such as atmospheric plasma spraying APS) has been gradually introduced into the field of plasma protection. It can achieve low-cost, high-efficiency, and continuous deposition by constructing ceramic coatings with a thickness of tens to hundreds of microns on the surface of equipment components, and has strong engineering adaptability. Aluminum oxide or yttrium oxide ceramic coatings prepared by thermal spraying have good heat resistance and chemical stability, especially in the early stages, showing considerable protection against fluorine-containing plasmas, and are widely used in etching equipment larger than 8 inches. Despite this, Y2O3 coatings prepared by existing thermal spraying technology generally have microscopic pores, which are prone to microcracks and peeling under high-power plasma bombardment, forming a large number of microparticles, contaminating the wafer surface, and causing a decrease in process yield; and for plasma-etching-resistant coatings prepared by thermal spraying, in order to achieve better etching resistance, the coating must have a thicker thickness (hundreds of microns), which will greatly increase the production cost of the plasma-etching-resistant coating.
[0004] Therefore, there is an urgent need to develop a new plasma protective coating system that combines high density, excellent insulation, long-life corrosion resistance and low cost advantages to solve the limitations of existing technologies in high-power, large-size cavity environments and promote semiconductor etching processes to higher processes. Summary of the Invention
[0005] In response to the above-mentioned problems, the present invention aims to provide a nanostructured plasma protective composite coating and preparation method, aiming to solve the problems of poor etching resistance, insufficient coating density, weak adhesion to the substrate, poor thermal stability, and high cost due to thick coatings in existing plasma protective coatings during semiconductor manufacturing. The present invention uses a vacuum cold spraying method to prepare a thin yttrium oxide composite coating on a substrate, and combines it with a heat treatment process to improve the density and etching resistance of the composite coating. The coating has a reasonable structural design, a stable material system, and a controllable preparation process. It can provide excellent protection performance in high-energy environments such as plasma etching, extend device life, and improve the process window and integrated reliability.
[0006] To achieve the above-mentioned purpose, the present invention first provides a nanostructured plasma protection composite coating, which is a composite ceramic coating prepared on a substrate by a vacuum cold spraying method. The thickness of the composite ceramic coating is 1~50μm, the grain size is 10~200nm, and the porosity is <1%. The composite ceramic coating material is composed of yttrium oxide and a second ceramic component, the mass fraction of yttrium oxide is 50~95%, and the second ceramic component is one or a combination of two or more of aluminum oxide, cerium oxide, lanthanum oxide, zirconium oxide, erbium oxide, gadolinium oxide, yttrium fluoride, yttrium oxyfluoride and yttrium aluminum garnet.
[0007] In one embodiment of the present invention, the composite coating material is a mixed powder prepared by mixing yttrium oxide powder and a second ceramic component by mechanical ball milling. The particle size of the yttrium oxide powder in the mixed powder is 0.1~5μm, preferably 0.2~2μm, and further preferably 0.3~1μm. The particle size of the second phase powder in the mixed powder is 10~200 nm, preferably 20~100nm.
[0008] In one embodiment of the present invention, the composite coating material is yttrium oxide coated with a second ceramic component, and the thickness of the coating layer is 5-50 nm, preferably 10-30 nm.
[0009] In one embodiment of the present invention, the yttrium oxide coated with the second ceramic component is prepared by a chemical method, which specifically includes the following steps: (1) Dispersing yttrium oxide powder in deionized water or ethanol and treating with ultrasound and mechanical stirring to form a stable suspension; (2) preparing a salt solution corresponding to the second ceramic component; (3) slowly adding the salt solution in step (2) to the suspension in step (1), while slowly adding a precipitant dropwise to carry out a precipitation reaction; (4) The reaction system was allowed to stand for aging and then dried at a low temperature of 60-80°C to remove the solvent; (5) The system obtained in the drying step (4) was calcined at 400°C for 12 hours to obtain a yttrium oxide composite powder coated with the second ceramic component.
[0010] In one embodiment of the present invention, in step (1), the mass volume ratio of yttrium oxide powder to deionized water or ethanol is 1:10 to 1:100.
[0011] In one embodiment of the present invention, in step (3), the concentration of the salt solution is 0.05-0.5 mol / L, and the volume ratio of the salt solution to the suspension is 1:10.
[0012] In one embodiment of the present invention, the precipitant in step (3) is selected from one of ammonia water, urea, and acetic acid, and the pH value of the solution is adjusted to 4-10.
[0013] In one embodiment of the present invention, the precipitation reaction in step (3) is carried out at a temperature of 50-90° C. and for a time of 1-10 h.
[0014] In one embodiment of the present invention, the thickness of the composite coating is preferably 5-15 μm, and the grain size is preferably 20-30 nm.
[0015] In one embodiment of the present invention, the mass fraction of the yttrium oxide is preferably 80-90%.
[0016] In one embodiment of the present invention, the substrate includes but is not limited to any one of ceramics, metals, glass, and polymer plastics.
[0017] The present invention also discloses a method for preparing the composite coating, which comprises the steps of firstly preparing the composite ceramic coating on a substrate by a vacuum cold spraying method, and then heat-treating the composite ceramic coating.
[0018] In one embodiment of the present invention, the working gas used in the vacuum cold spraying process is nitrogen or compressed air, the gas flow rate is 5-50 L / min, the spraying distance is 3-20 mm, and the powder feeding rate is 0.1-5 g / min.
[0019] In one embodiment of the present invention, the heat treatment temperature is 400-1000° C., preferably 600-800° C., and the time is 1-10 h, preferably 2-5 h.
[0020] The present invention also provides an application of the plasma protection composite coating in semiconductor devices.
[0021] In one embodiment of the present invention, the application includes use as a plasma etching protective coating.
[0022] Beneficial effects: (1) The present invention selects yttrium oxide and a second ceramic component for composite, introduces a second ceramic powder accounting for 5 to 50% of the total mass of the powder into the yttrium oxide, and adopts a vacuum cold spraying method to prepare a coating and then performs heat treatment. The composite coating prepared by this method has excellent fluorine / chlorine plasma corrosion resistance; nano-grain refinement significantly improves the density, thermal shock resistance, and micro-stability of the coating, and effectively reduces the formation of particulate pollutants; the vacuum cold spraying process has no melting at low temperature, avoids material structure degradation, and is suitable for heat-sensitive substrates and high-precision requirements; the material system is flexible and adjustable, adaptable to the protection needs under different process environments, and has the potential for industrial application.
[0023] (2) Mechanically mixing yttrium oxide and the second phase ceramic component or coating yttrium oxide with the second ceramic component to prepare a composite powder, and then using vacuum cold spraying technology combined with heat treatment can help obtain an etching-resistant coating with high coating bonding strength, and at the same time help improve the etching resistance of the coating.
[0024] (3) The composite coating with a lower thickness prepared by the method of the present invention has a lower preparation cost on the one hand, overcoming the inherent prejudice that a thicker coating can increase the etching resistance of the coating. On the other hand, the composite coating with a reduced thickness helps to further improve the bonding strength and etching resistance of the coating.
[0025] (4) The present invention constructs a nanostructured plasma protection composite ceramic coating system and proposes an efficient, low-loss, and controllable preparation method, providing a new material solution for plasma etching protection in semiconductor device manufacturing. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The surface morphology of the cerium oxide / yttrium oxide composite coating after etching in Example 1; Figure 2 This is the surface morphology of the yttrium oxide coating after etching in Comparative Example 1; Figure 3 It is a nanostructured plasma protection composite coating structure, wherein 1 is a substrate and 2 is a plasma protection composite coating. DETAILED DESCRIPTION
[0027] The present invention will be described in detail below with reference to specific embodiments. The following examples will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those skilled in the art, several changes and improvements can be made without departing from the scope of the present invention. These all fall within the scope of protection of the present invention.
[0028] The nanostructured plasma shielding composite coating provided by the embodiment of the present invention is suitable for surface protection of inner wall components of a semiconductor etching equipment chamber.
[0029] The coating thicknesses in the Examples and Comparative Examples were measured by observing cross-sections of the coatings using a scanning electron microscope (SEM). Cross-section samples were prepared and 10 measurement points were selected at different locations along the coating. Data was then read and analyzed using image analysis software to determine the average thickness of each layer. Porosity was determined by obtaining SEM images of the coating cross-sections and using grayscale threshold segmentation to identify and quantify pore areas. The average porosity was then determined by calculating the ratio of black and white pixel areas. Grain size and coating bond strength were measured on three samples, and the results were averaged.
[0030] Example 1 A nanostructured plasma shielding composite coating 2 is prepared on a substrate 1 by vacuum cold spraying. The coating material is a mixed powder of cerium oxide and yttrium oxide. The powder particle size D50 of yttrium oxide is 0.8 μm, and the powder particle size of cerium oxide is 30 nm. The mixing ratio of the two is 3:17, that is, the mass proportion of submicron yttrium oxide is 85%, and the mass proportion of nano-cerium oxide is 15%. The mixed powder is prepared by mechanical ball milling.
[0031] A method for preparing a nanostructured plasma protective composite coating is disclosed. The protective composite coating is prepared by vacuum cold spraying. During coating preparation, nitrogen is used as the working gas, the gas flow rate is 25 L / min, the spraying distance is 10 mm, and the powder feeding rate is 1.5 g / min. The composite coating is heat treated at 700°C for 2 hours.
[0032] After characterization and analysis, the results showed that the overall thickness of the composite coating was about 10 μm, the porosity was about 0.8%, the grain size was about 28 nm, and the coating bonding strength was about 20 MPa; after etching for 10 hours in CF4 / O2 atmosphere, the Figure 1 As shown, there are evenly distributed nanoscale etching marks on the surface of the composite coating, indicating that the coating is evenly etched with an etching rate of about 2.4 nm / min.
[0033] Example 2 The difference between Example 2 and Example 1 is that the coating material is a mixed powder of yttrium oxide and yttrium oxyfluoride. In the mixed powder, the particle size D50 of the yttrium oxide powder is 1.2 μm, and the particle size D50 of the yttrium oxyfluoride powder is 200 nm. The mass ratio of the two is 2:3, that is, the mass proportion of yttrium oxide is 60%, and the mass proportion of yttrium oxyfluoride is 40%. The composite powder is obtained by mechanical ball milling for 10 minutes.
[0034] A method for preparing a nanostructured plasma protective composite coating is disclosed. The protective composite coating is prepared by vacuum cold spraying. During coating preparation, nitrogen is used as the working gas, the gas flow rate is 35 L / min, the spraying distance is 15 mm, the powder feeding rate is 2.5 g / min, and the composite coating is heat treated at 800°C for 2 hours.
[0035] After characterization and analysis, the results showed that the overall thickness of the composite coating was about 25 μm, the porosity was about 1%, the grain size was about 38 nm, and the coating bonding strength was about 18 MPa; after etching for 10 hours in a CF4 / O2 atmosphere, the surface of the composite coating was uniformly etched at an etching rate of about 3.4 nm / min.
[0036] Example 3 A nanostructured plasma protection composite coating is prepared by a vacuum cold spraying method. The coating material is yttrium oxide composite powder coated with aluminum oxide, and the particle size D50 of the yttrium oxide powder is 0.4 μm.
[0037] The composite powder was prepared as follows: First, yttrium oxide powder with a particle size (D50) of 0.4 μm was dispersed in ethanol and ultrasonically dispersed for 20 minutes to prepare an yttrium oxide suspension. Aluminum sol prepared from aluminum nitrate was slowly added dropwise to the yttrium oxide suspension. The solution temperature was maintained at 60°C and the reaction was allowed to proceed for 6 hours. The precipitate was filtered, dried, and calcined at 400°C for 12 hours. The resulting composite powder had a particle size (D50) of approximately 0.43 μm and an alumina coating layer approximately 10 nm thick.
[0038] A method for preparing a nanostructured plasma protective composite coating is disclosed. The protective composite coating is prepared by vacuum cold spraying. During coating preparation, nitrogen is used as the working gas with a gas flow rate of 30 L / min, a spraying distance of 15 mm, and a powder feeding rate of 2.1 g / min. The composite coating is heat treated at 800°C for 5 hours.
[0039] After characterization and analysis, the results showed that the overall thickness of the composite coating was about 15 μm, the porosity was about 0.3%, the grain size was about 35 nm, and the coating bonding strength was about 26 MPa; after etching for 10 hours in a CF4 / O2 atmosphere, the surface of the composite coating was uniformly etched at an etching rate of about 2.7 nm / min.
[0040] Example 4 The difference between Example 4 and Example 3 is that the coating material is yttrium oxide composite powder coated with yttrium fluoride, and the particle size D50 of the yttrium oxide powder is 0.6 μm.
[0041] The composite powder was prepared as follows: First, yttrium oxide powder with a particle size (D50) of 0.6 μm was dispersed in deionized water and ultrasonically dispersed for 20 minutes to prepare an yttrium oxide suspension. A 0.1 mol / L aqueous ammonium fluoride solution was slowly added dropwise to the yttrium oxide suspension. The reaction was maintained at 60°C for 12 hours. The precipitate was filtered, dried, and calcined at 400°C for 12 hours. The resulting composite powder had a particle size (D50) of 0.6 μm and an yttrium fluoride coating thickness of approximately 30 nm.
[0042] The coating was prepared by vacuum cold spraying technology, with nitrogen as the working gas, a gas flow rate of 10 L / min, a spraying distance of 5 mm, a powder feeding rate of 0.5 g / min, and the composite coating was heat treated at 600 °C for 2 h.
[0043] After characterization and analysis, the results showed that the overall thickness of the composite coating was about 5 μm, the porosity was about 0.5%, the grain size was about 18 nm, and the coating bonding strength was about 24 MPa; after etching for 10 hours in a CF4 / O2 atmosphere, the surface of the composite coating was uniformly etched at an etching rate of about 1.7 nm / min.
[0044] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that only the yttrium oxide layer is formed on the substrate by using the vacuum cold spraying method.
[0045] High-purity yttrium oxide powder with a D50 particle size of 0.8 μm was used directly for spraying without composite coating treatment.
[0046] The coating was prepared using vacuum cold spraying technology, using nitrogen as the working gas, a gas flow rate of 25 L / min, a spray distance of 10 mm, and a powder feed rate of 1.5 g / min. After spraying, it was heat treated at 700°C for 2 hours. The coating deposition thickness was 11 μm, the porosity was approximately 0.9%, and the overall coating was relatively dense, with a grain size of 80 nm. The bonding strength was measured to be 10 MPa, which is lower than the composite sample (20 MPa). Plasma etching experiments (CF4 / O2 atmosphere, etching time 8 hours) tested, such as Figure 3 As shown in the figure, there are etching micro-pits on the surface of the composite coating, the etching rate is 3.8 nm / min, and it can be observed that part of the coating has fallen off.
[0047] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that the mixing ratio of cerium oxide and yttrium oxide is 1:49, that is, the mass proportion of submicron yttrium oxide is 98%, the mass proportion of nano cerium oxide is 2%, and the mixed powder is prepared by mechanical ball milling.
[0048] A method for preparing a nanostructured plasma protective composite coating is disclosed. The protective composite coating is prepared by vacuum cold spraying. During coating preparation, nitrogen is used as the working gas, the gas flow rate is 25 L / min, the spraying distance is 10 mm, and the powder feeding rate is 1.5 g / min. The composite coating is heat treated at 700°C for 2 hours.
[0049] After characterization and analysis, the results showed that the overall thickness of the composite coating was about 8 μm, the porosity was about 1%, the grain size was 75 nm, and the coating bonding strength was about 15 MPa; after etching for 10 hours in a CF4 / O2 atmosphere, the Figure 1 As shown, there are evenly distributed nanoscale etching marks on the surface of the composite coating, indicating that the coating is evenly etched with an etching rate of about 4.2 nm / min.
[0050] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that the coating thickness is 60 μm.
[0051] After testing, the porosity of the composite coating was about 0.9%, the grain size was 30 nm, and the coating bonding strength was about 19 MPa; after etching for 10 hours in a CF4 / O2 atmosphere, the surface of the composite coating was uniformly etched at an etching rate of about 4.6 nm / min, but the coating cracked and fell off.
[0052] Comparative Example 4 The difference between Comparative Example 4 and Example 3 is that a nanostructured plasma protection composite coating is prepared by a vacuum cold spraying method, the coating material is an aluminum oxide-coated yttrium oxide composite powder, the yttrium oxide powder particle size D50 is 0.4 μm, and the thickness of the aluminum oxide coating layer is 55 nm.
[0053] The composite powder was prepared as follows: First, yttrium oxide powder with a D50 of 0.4 μm was dispersed in ethanol and ultrasonically dispersed for 20 minutes to prepare an yttrium oxide suspension. Aluminum sol prepared from aluminum nitrate was slowly added dropwise to the yttrium oxide suspension. The solution temperature was maintained at 60°C and the reaction was allowed to proceed for 12 hours. The precipitate was filtered, dried, and calcined at 400°C for 12 hours. The resulting composite powder had a particle size D50 of approximately 0.43 μm and an alumina coating layer approximately 55 nm thick.
[0054] A method for preparing a nanostructured plasma protective composite coating is disclosed. The protective composite coating is prepared by vacuum cold spraying. During coating preparation, nitrogen is used as the working gas with a gas flow rate of 30 L / min, a spraying distance of 15 mm, and a powder feeding rate of 2.1 g / min. The composite coating is heat treated at 800°C for 5 hours.
[0055] After characterization and analysis, the results showed that the overall thickness of the composite coating was about 30 μm, the porosity was about 0.5%, the grain size was 90 nm, and the coating bonding strength was about 23 MPa; after etching for 10 hours in a CF4 / O2 atmosphere, the surface of the composite coating was uniformly etched at an etching rate of about 8.1 nm / min.
[0056] Table 1 shows the experimental data for Examples 1-4 and Comparative Examples 1-4. As can be seen from Table 1, when the yttrium oxide coating is prepared solely by vacuum cold spraying, the plasma etching rate of an 11 μm thick yttrium oxide coating is approximately 3.8 nm / min. While the coating exhibits moderate etching resistance, its bonding strength is low, and the coating may detach during etching. Experiments have shown that additional heat treatment of the yttrium oxide coating helps increase its bonding strength, but also increases the grain size of the coating, further reducing the coating's etching rate.
[0057] In order to further improve the performance of the yttrium oxide coating that is easy to fall off, the present invention selects yttrium oxide and a second ceramic component for compounding, adopts the method of vacuum cold spraying to prepare the coating and performs heat treatment, which helps to obtain an etching-resistant coating with high coating bonding strength, and at the same time helps to improve the etching resistance of the coating. Mechanically mixing yttrium oxide and the second-phase ceramic component can further improve the etching resistance of the mixed powder, and combining with heat treatment can improve the bonding strength of the coating. It can be seen from Examples 1~2 and Comparative Examples 2~3 that the proportion of the second ceramic component has a great influence on the etching resistance of the final ceramic coating. Specifically, when the proportion of yttrium oxide is greater than 95%, due to the small proportion of the second ceramic component, it is difficult to significantly improve the etching resistance of the ceramic, and the etching resistance of the ceramic coating is still poor. When the proportion of yttrium oxide exceeds 50%, due to the poor etching resistance of the second phase or the weak bonding force with the substrate, the overall performance of the entire coating is also poor, which is difficult to meet actual needs.
[0058] Coating a second ceramic component on the surface of yttrium oxide can also help further improve the etching resistance of the yttrium oxide coating prepared by the vacuum cold spraying method. From the experimental results of Examples 3, 4 and Comparative Example 4, it can be seen that the coating thickness of the coated second ceramic component and the material of the second ceramic component have a significant impact on the etching resistance of the final coating. Specifically, when the coating thickness of the second ceramic component exceeds 30nm, especially when it exceeds 50nm, the etching resistance of the coating drops sharply, which can also be seen from the results of Example 3 and Comparative Example 4. If the second ceramic component is a material with better etching resistance, such as yttrium fluoride, yttrium oxyfluoride, etc., the etching resistance of the composite coating can be further improved. For example, the etching rate in Example 4 is as low as 1.7nm / min.
[0059] In addition, the thickness of the composite coating has a great influence on the preparation cost and coating performance of the coating. On the one hand, increasing the coating thickness will greatly increase the production cost of the coating. On the other hand, the better the coating thickness is, the better the etching resistance of the coating is. Experiments have shown that when the thickness of the composite coating increases to more than 50μm, the bonding strength and etching resistance of the coating show a downward trend.
[0060] Table 1 Comparison of coating parameters between the embodiment and the comparative example
[0061] The embodiments provided above are not intended to limit the scope of the present invention, nor are the steps described to limit their execution order. Any obvious improvements to the present invention made by those skilled in the art in combination with existing common knowledge shall fall within the scope of protection defined by the claims of the present invention.
Claims
1. A nanostructured plasma shielding composite coating, characterized in that: The composite coating is a composite ceramic coating prepared on a substrate by a vacuum cold spraying method. The thickness of the composite ceramic coating is 1~50μm, the grain size is 10~200nm, and the porosity is <1%. The material of the composite ceramic coating is composed of yttrium oxide and a second ceramic component. The mass fraction of the yttrium oxide is 50~95%, and the second ceramic component is one or a combination of two or more of aluminum oxide, cerium oxide, lanthanum oxide, zirconium oxide, erbium oxide, gadolinium oxide, yttrium fluoride, yttrium oxyfluoride and yttrium aluminum garnet.
2. The plasma shielding composite coating according to claim 1, wherein: The material of the composite ceramic coating is a mixed powder prepared by mixing yttrium oxide powder and a second ceramic component by mechanical ball milling. The particle size of the yttrium oxide powder in the mixed powder is 0.1-5 μm, and the particle size of the second phase powder in the mixed powder is 10-200 nm.
3. The plasma shielding composite coating according to claim 1, characterized in that: The material of the composite ceramic coating is yttrium oxide coated with a second ceramic component, the thickness of the coating layer is 5-50 nm, and the yttrium oxide coated with the second ceramic component is prepared by a chemical method.
4. The plasma shielding composite coating according to claim 1, wherein: The composite ceramic coating has a thickness of 5-15 μm and a grain size of 10-50 nm.
5. The plasma shielding composite coating according to claim 1, characterized in that: The mass fraction of the yttrium oxide is 80-90%.
6. The plasma shielding composite coating according to claim 1, characterized in that: The material of the substrate includes but is not limited to any one of ceramics, metals, glass, and polymer plastics.
7. A method for preparing a plasma shielding composite coating according to any one of claims 1 to 6, characterized in that: The method comprises the steps of firstly preparing a composite ceramic coating on a substrate by using a vacuum cold spraying method, and then performing heat treatment on the composite ceramic coating.
8. The preparation method according to claim 7, wherein The working gas used in the vacuum cold spraying process is nitrogen or compressed air, the gas flow rate is 5-50 L / min, the spraying distance is 3-20 mm, and the powder feeding rate is 0.1-5 g / min.
9. The preparation method according to claim 7, characterized in that The heat treatment temperature is 400-1000° C., and the time is 1-10 hours.
10. Use of the plasma protective composite coating according to any one of claims 1 to 6 as a plasma etching protective coating in a semiconductor device.
Citation Information
Patent Citations
Application of nanometer aluminum oxide-based composite ceramic coating
CN102443753A
Method for preparing IC equipment surface key part surface protective coating based on the plasma spraying and cold spraying technology
CN110468367A
Preparation method of oxide / oxide composite material surface environmental barrier coating
CN114000090A
Yttrium oxide-aluminum oxide transition layer composite ceramic as well as preparation method and application thereof
CN119430879A
Yttria-coated ceramic components of semiconductor material processing apparatuses and methods of manufacturing the components
CN1906026A
Cited By
Quartz glass product surface treatment method
CN122322962A
